Strategi Pemasaran dalam Meningkatkan Kinerja UMKM Kuliner: A Systematic Literature Review - Safitri, Rusni Azhari; Maulidya, Liva; Amelia, Putri; Alfariada, Elda Riska (Shofanah Media Berkah, 2026)
This study examines the role of marketing strategies in improving the performance of culinary MSMEs using a Systematic Literature Review approach. Scientific publications from 2020–2025 were collected through Publish or Perish and Google Scholar and analyzed using bibliometric methods and TF-IDF–based text mining. The findings indicate that marketing strategies, particularly digital marketing, marketing innovation, and market orientation, significantly enhance MSME competitiveness and performance. However, research linking marketing strategies to long-term business sustainability remains limited. This study provides a conceptual foundation for developing adaptive and sustainable marketing strategies for culinary MSMEs.